Measurement Properties of a Park Use Questionnaire. (May 2013) - Evenson, Kelly R.; Wen, Fang; Golinelli, Daniela; Rodríguez, Daniel A.; Cohen, Deborah A.
This study determined the criterion validity and test–retest reliability of a brief park use questionnaire. From five U.S. locations, 232 adults completed a brief survey four times and wore a global positioning system (GPS) monitor for 3 weeks. We assessed validity for park visits during the past week and during a usual week by examining agreement between frequency and duration of park visits reported on the questionnaire to the GPS monitor results. Spearman correlation coefficients (SCC) were used to measure agreement. For past week park visit frequency and duration, the SCC were .62 to .65 and .62 to .67, respectively. For usual week park visit frequency and duration, the SCC were .40 to .50 and .50 to .53, respectively. Usual park visit frequency reliability was .78 to .88 (percentage agreement: 69%-82%) and usual park visit duration was .75 to .84 (percentage agreement: 64%-73%). These results suggest that the questionnaire to assess usual and past week park use had acceptable validity and reliability.